The Gerire Hills, SE Ethiopia: ecology and phytogeographical position of an additional local endemic, Anacampseros specksii (Anacampserotaceae). Issue 2 (3rd July 2019) - Friis, Ib; Gilbert, Michael G.; Weber, Odile; Van Breugel, Paulo; Demissew, Sebsebe
ABSTRACT: Anacampseros specksii Dreher (Anacampserotaceae, in Flora of Ethiopia and Eritrea in Portulacaceae), was described in 2016 from plants grown from seeds collected from Bale, SE Ethiopia. The species was not included in the paper on the Gerire Hills published by the present authors in Webbia in 2018. A. specksii is here considered to be another narrow endemic species in the Gerire Hills, belonging to the group of species that grows on the edges of Monte Ellot and Bur Caddas on sandstone rocks eroding into loose gravel. Anacampseros vespertina, the only other species of Anacampseros in NE tropical Africa, grows on limestone gravel in Somalia near the Indian Ocean, whilst the south tropical African species, A. rhodesica, grows on granite rocks in Zimbabwe, Botswana, Mozambique and South Africa. The conservation assessment in 2016 for A. specksii was Data Deficient (DD) because only one population had been observed and the number of individuals is not known; this assessment is here discussed and maintained.